Adaptive isolated personal workstation pod - Azmin, Aida Kesuma (Asia International Community of Art & Design (AICAD), Faculty of Art & Design,Universiti Teknologi MARA, 2022)
When Covid-19 pandemic struck in 2020, it had affected many job sectors’ working norms.Employment and employability rate were also hugely affected from this outbreak. The movement control order demands new normal working environment, where people had to work fromhome (WFH). Inevitably, some still have to work from office (WFO) and sometimes, work outdoors (WO). However, there was never a properly designed isolated personal workstation that is tailored to adapt to these working conditions and may help reduce the risk of Covid-19 virus spread. Hence, in order to reduce employees' health risks, whilst maintaining work efficiency and flexibility at different work situations, the design project proposes “An Adaptable Personalised Workstation Pod” that is ergonomically designed, flexible and commutable (if needed) for different working conditions during pandemic control movement order. These innovative products are hoped to be the catalyst for safe and convenient working environments to withstand the pandemic health risks. TheWorkstation Pod sample shown here is one of the products of the project that is flexible enough to be opened, closed, interchange form, and if necessary, movable or transportable. Its size is a maximum of 2 metres (width) x 2 metres (length) x 2 metres (height). The sample product design shall be a prototypical example to many more personal workstation pods in the attempt to reduce the risks of covid-19 disease infection and increase work efficiency regardless of the pandemic threat.